Topical administration of a connexin43‐based peptide augments healing of chronic neuropathic diabetic foot ulcers: A multicenter, randomized trial. Issue 2 (29th April 2015) - Grek, Christina L.; Prasad, G.M.; Viswanathan, Vijay; Armstrong, David G.; Gourdie, Robert G.; Ghatnekar, Gautam S.
ABSTRACT Nonhealing neuropathic foot ulcers remain a significant problem in individuals with diabetes. The gap‐junctional protein connexin43 (Cx43) has roles in dermal wound healing and targeting Cx43 signalling accelerates wound reepithelialization. In a prospective, randomized, multicenter clinical trial we evaluated the efficacy and safety of a peptide mimetic of the C‐terminus of Cx43, alpha connexin carboxy‐terminal (ACT1), in accelerating the healing of chronic diabetic foot ulcers (DFUs) when incorporated into standard of care (SOC) protocols. Adults with DFUs of at least four weeks duration were randomized to receive SOC with or without topical application of ACT1. Primary outcome was mean percent ulcer reepithelialization and safety variables included incidence of treatment related adverse events (AEs) and detection of ACT1 immunogenicity. ACT1 treatment was associated with a significantly greater reduction in mean percent ulcer area from baseline to 12 weeks (72.1% vs. 57.1%; p = 0.03). Analysis of incidence and median time‐to‐complete‐ulcer closure revealed that ACT1 treatment was associated with a greater percentage of participants that reached 100% ulcer reepitheliazation and a reduced median time‐to‐complete‐ulcer closure. No AEs reported were treatment related, and ACT1 was not immunogenic. Treatment protocols that incorporate ACT1 may present a therapeutic strategy that safely augments the reepithelialization of chronic DFUs.